In-situ reduction of Cu(CH3COO)2 to prepare π-complexation adsorbent for propylene/propane separation by slurry bed. Issue 12 (13th August 2017) - Tian, Yuanyu; Zhou, Haifeng; Qiao, Yingyun; Tang, Ruiyuan; Zhao, Guoming; Leng, Guiling
ABSTRACT: A simple process by slurry bed and π-complexation adsorbent was developed for separation of propylene/propane mixtures. The adsorbent, Cu(I) immobilized active carbon (AC), was prepared by the in-situ reduction of Cu(CH3 COO)2 . The adsorption amount of propylene and selectivity was 35.1 mL/g and 1.57, 30.4 mL/g and 1.45 for Cu(CH3 COO)2 -AC-N2 (calcined in N2 atmosphere) and Cu(CH3 COO)2 -AC-Air, respectively. Compared with AC, the BET surface area decreased, while the average pore diameter increased. It suggested that the metal salt deposited at the entrance of pores, blocking part of pores. According to the results from IR, XRD and TPR, Cu2 O was the main copper species on the surface of the solid adsorbent.